Investigating the relationship between cancer and orofacial clefts using GWAS significant loci for cancers: A case-control and case-triad study - Fashina, Azeez; Busch, Tamara; Young, Mary; Adamson, Olawale; Awotoye, Waheed; Alade, Azeez; Adeleke, Chinyere; Hassan, Mohaned; Oladayo, Abimbola M.; Gowans, Lord J. J.; Eshete, Mekonen; Naicker, Thirona; et al. (Frontiers in Oral Health, 2022)
Background Several population-based case-control studies have reported concurrent presentation of cancer and congenital malformations. Many associations have been made between oral clefting and cancers, though some of these results are conflicting. Some studies have reported an increased risk of cancer among 1st-degree relatives of cleft cases and vice versa, and also an excess risk of cancers of the breast, lung, and brain among those with oral clefts. This study aimed to determine if the genetic polymorphisms found in some cancers are also associated with orofacial cleft in an African cohort. Methods The study was a case-control and case-triad study in which cases were 400 individuals clinically diagnosed with non-syndromic cleft lip and/or palate (CL/P), while controls were 450 individuals without CL/P. Samples were obtained from three African countries while DNA extraction, PCR, and genotyping were carried out at the University of Iowa, US. Eleven SNPs in genes coding for SWI/SNF subunits and 13 GWAS significant SNPs for cancers associated with orofacial cleft were selected. Case-control analysis, transmission disequilibrium test (TDT), and DFAM to combine the parent-offspring trio data and unrelated case/control data in a single analysis were carried out using PLINK. Results For the case-control analyses that included all the clefts and for the CLP subtype, none of the SNPs were statistically significant. Statistically increased risk for the following SNPs rs34775372 (p = 0.02; OR = 1.54, CI:1.07–2.22), rs55658222 (p = 0.009; OR = 2.64, CI:1.28–5.45) and rs72728755 (p = 0.02; OR=2.27, CI:1.17–4.45) was observed with the CL only sub-group. None of these were significant after Bonferoni correction. In the TDT analyses, a significantly reduced risk with rs10941679 (p = 0.003; OR = 0.43, CI:0.24–0.75) was observed and this was significant after Bonferroni correction. The rs10941679 was also significant (p = 0.003) in the DFAM analyses as well even after Bonferroni correction. Conclusion The results from this study represent an important starting point for understanding the concurrent presentation of some cancers in orofacial clefts, and cancer risks in cleft patients. The associations observed warrant further investigation in a larger cohort and will set the stage for a more mechanistic approach toward understanding the risk for cancers in families with clefts.